A research analysis of the difference of opinion among the jurists and mystics about the disputed matters in the light if Tafseer Room am Ma'ani - Wali Zaman; Fakhar ud Din (Hazara Islamicus, 2021)
A scholarly review of dissentious tenets between jurisprudents and Sufis in the light of “Ruhol Maani”.Mahmood bin Abdullah Aloosi is a well-known scholar of the Islamic world. his nickname is Shehab u din. he wrote more than twenty-two books on different topics. one of his famous books is Ruhol maani in Tafseer. in Tafseer he described various issues of Islamic education, such as serf. nahv, balaghat etc. he also described the dissentious tenets between jurisprudents and Sufis. in this article we have mentioned some of such tenets.